2010
DOI: 10.1002/nau.20905
|View full text |Cite
|
Sign up to set email alerts
|

Raising awareness about fecal incontinence

Abstract: There is a lack of awareness about fecal incontinence despite its prevalence and adverse impact on quality of life. Inadequate knowledge about fecal incontinence deters help-seeking, therapeutic consultation, and clinical research about effective prevention and management strategies. A systematic, evidenced-based approach to raise awareness of fecal incontinence is essential to forward progress and overcome multiple barriers. In this manuscript, strategies of this approach are prioritized and focus on increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 28 publications
1
23
0
1
Order By: Relevance
“…Only 2.7 percent of patients with selfreported FI also had a medical diagnosis (30). The extent to which this problem is explained by limited awareness of the prevalence, burden, and management of FI, by insufficient time during visits or by other factors is unknown (31). There is a lack of consensus on how to screen for FI.…”
Section: Healthcare Seeking Behavior In Fimentioning
confidence: 99%
See 1 more Smart Citation
“…Only 2.7 percent of patients with selfreported FI also had a medical diagnosis (30). The extent to which this problem is explained by limited awareness of the prevalence, burden, and management of FI, by insufficient time during visits or by other factors is unknown (31). There is a lack of consensus on how to screen for FI.…”
Section: Healthcare Seeking Behavior In Fimentioning
confidence: 99%
“…Conversely, less frequent and less severe FI (8), and lower embarrassment as measured by the FIQOL questionnaire (29) are associated with lower rates of consulting. Barriers to seeking care include a lack of understanding of the term fecal incontinence, embarrassment, the belief that FI is a normal part of aging, unfamiliarity with whom to discuss this problem, priority of other medical conditions, concerns that there are no options to treat FI, and pessimism that physicians will be able to help (8, 29, 31). For example, an internet-based survey observed that only 30% of nearly 1100 community dwelling women with FI had heard the term “fecal incontinence”; a majority (71%) preferred the term “accidental bowel leakage” to describe their condition (14).…”
Section: Healthcare Seeking Behavior In Fimentioning
confidence: 99%
“…Only half of FI‐affected elderly people had sought medical attention, and the majority of influencing variables were need factors. This shows a low awareness of FI in Asia, indicating that people may have limited awareness of appropriate assessments and treatment options, but could also be related to a lack of inquiry about FI by health care providers . Regarding the aging population, understanding the epidemiology of FI and factors associated with help seeking for this widespread problem are beneficial in devising and implementing prevention and management strategies.…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of FI is similar in men and women and increases with age until it plateaus at about 15% in the sixth decade of life [36-37]. Unless asked, a majority of patients will not volunteer the symptom to their physicians [38-40] (Table 2). Reinforcing previous studies [41-42] ••, preliminary reports suggest that “urgency” and “frequency of bowel motions” were ranked the most important symptoms by women with FI [43].…”
Section: Fecal Incontinencementioning
confidence: 99%